2003
DOI: 10.1016/s0378-1097(03)00380-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of polyphenols with immobilized Candida tropicalis under metabolic induction

Abstract: During olive oil production, large quantities of olive mill wastewater (OMW) are produced. This wastewater material, containing a high level of phenolic compounds, poses a serious environmental problem in almost all Mediterranean countries. Candida tropicalis YMEC14 was used as an extremophile strain to design an aerobic biotreatment process to detoxify OMW and reduce its polluting organic load. The process was enhanced by directing yeast metabolism towards biodegradation pathways using hexadecane as co-metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 23 publications
5
49
1
2
Order By: Relevance
“…Lanciotti et al (2005), using Yarrowia lipolytica, obtained 41% COD reduction on undiluted OMW. Ettayebi et al (2003) have reported similar results with 70% COD reduction although they used diluted OMW supplemented with nutrients. The highest COD reduction on undiluted OMW was obtained by Scioli and Vollaro (1997) who obtained 80% COD reduction on OMW supplemented with ammonium sulphate and yeast extract using the culture collection yeast Yarrowia lipolytica ATTC 20255.…”
Section: Yeast Treatment Of Omwmentioning
confidence: 65%
See 1 more Smart Citation
“…Lanciotti et al (2005), using Yarrowia lipolytica, obtained 41% COD reduction on undiluted OMW. Ettayebi et al (2003) have reported similar results with 70% COD reduction although they used diluted OMW supplemented with nutrients. The highest COD reduction on undiluted OMW was obtained by Scioli and Vollaro (1997) who obtained 80% COD reduction on OMW supplemented with ammonium sulphate and yeast extract using the culture collection yeast Yarrowia lipolytica ATTC 20255.…”
Section: Yeast Treatment Of Omwmentioning
confidence: 65%
“…Moreover, they seem to be the dominant microorganisms in this wastewater compared to bacteria and moulds (Ben Sassi et al 2005). Collection yeasts such as Yarrowia lipolytica (Lanciotti et al 2005) as well as isolates from the olive wastes such as Candida tropicalis (Ettayebi et al 2003) and Geotrichum candidum (Assas et al 2002) led to significant reduction of polyphenols and COD in OMW.…”
Section: Introductionmentioning
confidence: 98%
“…Hamdi (1992) reported that phenols, responsible for OMW's black colour, present little toxicity and are not biodegradable. Other studies regarding the dephenolization of OMW, or production of valuable products, using as source an OMW effluent, used other C. oleophila yeast related species (Lanciotti et al, 2005;Fadil et al, 2003;Ettayebi et al, 2003;D'Annibale et al, 2006;Papanikolaou et al, 2007). These works have proven that phenol removal from OMW by yeasts seems to be a strain-dependent process (Papanikolaou et al, 2007), since in similar conditions some yeast strains are able and others cannot grow in media with OMW, even when the amount of phenolic compounds is low.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster BII was composed only of L25 located in a separate group forming a monophyletic subclade with C. tropicalis bootstrap at 99.8% (Figure 2). C. tropicalis has been used in biotechnology, due to its ability to degrade hydrocarbons, ferment cocoa beans (Ardhana and Fleet, 2003), degrade polyphenols in wast water (Ettayebi et al, 2003), and produce polyhydroxybutyrate (Priji et , 2013). Further, C. tropicalis has been isolated from the rumens of goats (Priji et al, 2013).…”
Section: Molecular Characterizationmentioning
confidence: 99%